Strain‐Engineering of Contact Energy Barriers and Photoresponse Behaviors in Monolayer MoS2 Flexible Devices. (9th September 2020) - Pak, Sangyeon; Lee, Juwon; Jang, A‐Rang; Kim, Seungje; Park, Kyung‐Ho; Sohn, Jung Inn; Cha, SeungNam
Abstract: Flexible electronics and optoelectronics based on monolayered, semiconducting transition metal dichalcogenides (TMDCs) channel have recently received attention as the 2D structure possess superior mechanical, optical, and electrical properties. However, there is a lack of understanding of strain‐dependent electrical and photoelectrical properties in the electrode‐TMDC channel system. Here, two‐terminal flexible device is fabricated and strain‐engineered contact barrier modulation between monolayer MoS2 channel and Au electrode is shown. It is found experimentally through in situ strain electrical and kelvin probe force microscope measurements that tensile strain lowers the contact energy barriers between MoS2 and Au, in which the changes in the contact barriers is attributed to the strain‐induced increase of the electron affinity in MoS2 monolayer. Furthermore, the strain‐induced barrier modulation is also shown to affect photoresponse behaviors in a MoS2 flexible photodetectors through bending of energy bands that affect photogenerated carrier transport and electron‐hole recombination. These findings present important pathway toward designing flexible devices based on 2D TMDCs. Abstract : Upon applied tensile strain, the Schottky barrier of a MoS2 flexible device is lowered due to an increase in electron affinity of MoS2, which is proven using in situ strain‐electrical, KPFM, and photoresponse measurements. Furthermore, the modulated Schottky barrier affects photoresponse behaviors by affecting photogenerated carrier transport and electron‐hole recombination. These findings present important pathway toward designing flexible 2D devices.